Growth of ZnO Nanorods Coated Carbon Nanotubes Structures by Aqueous Solution Method - Yu, Naisen; Xiong, Wenjie; Cong, Yan; Wu, Yunfeng (Asian Journal of Chemistry, 2011)
Zinc oxide (ZnO) nanostructures are grown on carbon nanotubes (CNTs) using low temperature aqueous solution method. The growth is carried out in a two-step process, including synthesizing ZnO seeding layer and forming ZnO nanorods. Scanning electron microscopy (SEM) shows the ZnO nanorods have well-distributedly grown on the carbon nanotubes. The field electron emission of carbon nanotubes and ZnO-coated carbon nanotubes are also measured. The results show that ZnO nanostructures grown onto carbon nanotubes exhibit a high emission current density and field-enhancement factors, which make it a potential candidate for further applications.